A Pilot Study of a Self-Management Support Intervention in Middle-Aged Women with Knee Osteoarthritis - Bunsanong, Thippawan; Chaimongkol, Nujjaree; Deoisres, Wannee (Journal of The Royal Thai Army Nurses, 2021)
This pilot study of one-group pre-experimental design with pretest-posttest and follow-up measures aimed to test feasibility of a self-management support intervention comparing 3-time measuring scores of knee functional status and health related quality of life (HRQOL) among middle-aged women with knee osteoarthritis. A convenience sampling technique was used to recruit participants including five middle-aged women who have been clinically diagnosed with knee OA in Nakhon Si Thammarat province. Participants received a self-management support intervention of all 8 sessions for 4 weeks, and 4-week follow-up. Data were analyzed by using Friedman with Dunn-Bonferroni post hoc test. The results revealed that there are significant differences over the three-time measures of the outcomes. Scores of Knee functional status and HRQOL at follow-up period (T3) was significantly greater than that at baseline (T1) (p<.05) while no difference was found between posttest (T1) and baseline (T2), and posttest (T2) and follow-up (T3) measurement. These findings indicate this self-management support intervention is feasible in nursing clinical practice for further implementation.